2015
DOI: 10.1093/nar/gkv1028
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the striking difference in twist-stretch coupling between DNA and RNA: A comparative molecular dynamics analysis

Abstract: Double stranded helical DNA and RNA are flexible molecules that can undergo global conformational fluctuations. Their bending, twisting and stretching deformabilities are of similar magnitude. However, recent single-molecule experiments revealed a striking qualitative difference indicating an opposite sign for the twist-stretch couplings of dsDNA and dsRNA [Lipfert et al. 2014. Proc. Natl. Acad. Sci. U.S.A. 111, 15408] that is not explained by existing models. Employing unconstrained Molecular Dynamics (MD) si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
123
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(137 citation statements)
references
References 63 publications
12
123
2
Order By: Relevance
“…2B) showed that as the force increases, DNA overwinds and RNA unwinds. Although counterintuitive, this behavior is in agreement with previous experimental and theoretical works (2,3,5,19). The slope of a linear fit to the helical twist data provided a measurement of −g=CS (Fig.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…2B) showed that as the force increases, DNA overwinds and RNA unwinds. Although counterintuitive, this behavior is in agreement with previous experimental and theoretical works (2,3,5,19). The slope of a linear fit to the helical twist data provided a measurement of −g=CS (Fig.…”
Section: Resultssupporting
confidence: 91%
“…We performed all-atom MD simulations using the 16-mer dsDNA and dsRNA molecules used by Liebl et al (19). Molecules were neutralized with 30 sodium counter-ions and placed in a cubic box with dimensions of ∼80 Å × 80 Å × 80 Å, which was then filled with explicit water molecules.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations